Les transitions vers l'enseignement supérieur de jeunes d'origine étrangère à Bruxelles - Perrine Devleeshouwer (Nantes Université, 2016)
This article analyses the upward social mobility wishes through higher education of youth with a migrant background in Brussels. Based on the literature about higher aspiration of migrant populations, the article demonstrates that the link between aspirations and migratory projects is non-systematic. This links is mediated by the educational experience - intended here as both the students' position in the educational hierarchies and the subjective perceptions they have about their position. The article also shows the students' tinkering strategies when they face contingencies in their transition to higher education.